Faktor-Faktor yang Mempengaruhi Penghindaran Pajak pada Perusahaan Food and Beverage - Lucia Ari Diyani; Huda Aulia Rahman (Studi Akuntansi dan Keuangan Indonesia, 2022)
This study aims to examine the effect of advertising expense, capital intensity, and sales growth on tax avoidance and uses firm size as a moderating variable. The research population comes from the food & beverage sector which is one of the government's priorities as a driving force for the national economy. The company is listed on the Indonesia Stock Exchange for eight periods, namely 2013-2020. This research is a causal research and uses quantitative methods which are processed using panel data regression analysis techniques. The results show that sales growth has a positive impact on tax avoidance, while advertising expenses and capital intensity have no impact. Then, company size is only able to moderate the effect of sales growth on tax avoidance.